Committee heads suggest museum site on First St. - Eaton, Scott (Raton, NM Raton Range, 1976)
This article is about a committee developed to find a possible site for the museum.
Newspaper Article
Master list item #: 67
File location is in the Raton file Cabinet
Keywords: Mercantile, Tinnie; Anderson, Phelps; Gurule, Robert -- Mayor; DiLisio, Harriet; Stockton, Alvin; Anderson, Robert O; Hunt, Don -- Place Manager; Ames, Neil; Crump, Leola; McGarvey, Hannah; Raton Museum; Raton City Commission; Tinnie Mercantile Company; Palace Restaurant; Colfax County Society of Art, History and Archeology; State Planning Office; Committee Findings; Museum Location; Possible Sites; Business Futures; South Fisrt Street; Coors Building; Haven Hotel; Shuler House; Raton, New Mexico